The Study on the Growth Rate and Peat Characteristics of Chilli Plantation Utilising Coconut Husk and Peanut Shell as Sustainable Alternative to Soil Cultivation - NARMATDEVI SHANMUGAM,; NOR FAIZAH BINTI RAZALI , (Progress in Engineering Application and Technology, 2023)
Soilless media, method of growing plants without the use of soil as a rooting medium, is the most intensive and effective production method in the modern agriculture industry. Soilless cultivation has been observed to be an effective way to improve product quality. Thus, this research used agriculture waste of Cocopeat and Peanut Shell as an alternative to soil cultivation. The main objective of this study was to observed the chilli plantation growing rate by using coconut and peanut husk as a peat and identified physical and chemical characteristics of growing media. The 5 different treatment media was used in this study with different ratios. All the treatments were characterised in the aspects of pH, electrical conductivity, bulk density, particle density, moisture content and water holding capacity. For the observation of growth rate number of chilies, leaves, flowers and height of plants were determined after harvesting. The treatment with mixing ratios at T4 (50%: 50%) and T5 (60%: 40%) of cocopeat and peanut shell showed a better performing than 100% of soil, cocopeat and peanut shell. It exhibited appropriate values for the physical properties of T4 and T5 which are for the pH (6.11, 5.51), EC (0.0089, 0.0091), BD (0.194, 0.2) g/ , PD (0.587, 0.554) g/ , MC (48.66, 53.08)%, WHC (59.75, 64.79)% which was very close to the standard of soilless medium. It is observed that the growth rate of plant was achieved in T4 and T5 with the number of 6 and 7 chillies produced. The recommended usage of peanut shell was below 50% due to its undesirable physical properties. Other organic matter and properties of medium produced can be further investigated in future.